Implementation of Academic Quality Management Through the PDCA Cycle at SD Negeri Pringapus 02 Semarang Regency - Jaya Yanti Nur Istiqomah; Maryanto; Ghufron Abdullah (SOSIOEDUKASI, 2025)
This study explores the implementation of academic quality management at SD Negeri Pringapus 02, Pringapus District, Semarang Regency, using a qualitative case study approach. Data were collected through interviews, observation, and documentation with principals, teachers, committees, and supervisors. The findings show that quality management is applied consistently through the PDCA (Plan–Do–Check–Action) cycle. Planning is conducted in annual meetings involving stakeholders to design programs on teacher recruitment, curriculum evaluation, student admission, and infrastructure development. Implementation includes the Merdeka Curriculum, balanced teacher–student ratio, extracurricular and co-curricular activities, and continuous improvement of facilities. Monitoring is carried out through academic supervision by the principal, while corrective actions include coaching, in-house training, workshops, and teacher professional development. The study concludes that PDCA enhances teacher competence, school performance, and student achievement. It emphasizes participatory leadership and a quality-oriented culture while recommending future studies across diverse school contexts.